Chemical Profiles and Biological Activities of Essential Oil from Serissa japonica - Ty Viet Pham; Thien-Y Vu; Hien Minh Nguyen (Molecules)
This study was the first to analyze the chemical compositions and bioactivities of Serissa japonica leaf oil. The oil, obtained via hydro-distillation with a 0.1% yield, contained 64 compounds, predominantly non-terpenic compounds (39.0%), oxygenated sesquiterpenes (31.4%), and oxygenated monoterpenes (25.6%). Major constituents included 1,8-cineole, (E)-nerolidol, and iso-longifolol. The oil showed good antioxidant activity (IC50 ≈ 62.79 ± 0.77 µg/mL for DPPH and 57.82 ± 1.12 µg/mL for ABTS) and a good anti-tyrosinase effect (IC50 ≈ 195.6 ± 3.82 µg/mL). The trend was similar to anti-inflammatory activity, with an IC50 value of 63.03 ± 3.22, for NO inhibition without cytotoxicity at 100 µg/mL. The bovine serum albumin (BSA) blocking assay demonstrated an IC50 value of 59.31 ± 0.71 µg/mL, indicating a good interaction regarding enzyme inhibition. Moreover, the computational modeling of the possible association between tyrosinase and cyclooxygenase-2 highlighted their antioxidant and anti-inflammatory properties. The results pointed out the usefulness of S. japonica essential oil as a natural candidate for managing oxidative stress and inflammation.